Mixed Modeling in Genetic Divergence Study of Elite Popcorn Hybrids (Zea mays var. everta) - Guilherme Ferreira Pena; Gabrielle Sousa Mafra; Antônio Teixeira do Amaral Júnior; Rafael Ferreira Alfenas; Leonardo Lopes Bhering; Juliana Saltires Santos; Samuel Henrique Kamphorst; Valter Jário de Lima; Talles de Oliveira Santos; Rosimeire Barboza Bispo; Flávia Nicácio Viana; Messias Gonzaga Pereira; et al. (Agriculture, 2022)
Popcorn is a food highly appreciated throughout the world, generating billions of dollars annually just in the North American market alone. Even in the face of the historical superiority of American hybrids, which occupy almost 100% of the grain production fields in Brazil, our researchers have been working to develop cultivars that combine important traits for the crop, such as tolerance to leaf diseases and high rates of grain yield and popping expansion. This work investigated the degree of genetic divergence among 40 diallel hybrids of popcorn, 16 parents and 6 elite controls using mixed models to discriminate superior materials to be adopted in the Brazilian agribusiness. Based on the individual Best Linear Unbiased Prediction (BLUP) of each of the 15 variables analyzed, the Unweighted Pair-Group Method using Arithmetic Averages (UPGMA) and Tocher clusters were performed, and the study of Pearson correlation was carried out. The results pointed out that there is genetic variability among the genotypes evaluated and that the best candidates for composing superior genotypes are in the combination between the P10×L77 parents and/or between the P7 and L88 lines. Linear correlations showed that earlier flowering and taller genotypes exhibited an association with materials more tolerant to Exserohilum turcicum intensity.